Increasing Prayer Ability for Children in Cibeber Village, Sukagumiwang District, Indramayu Regency - Iko Rizqonah; Ibnudin; Ahmad Syathori (Quality : Journal Of Education, Arabic And Islamic Studies, 2023)
Prayer is a type of worship in the Islamic religion carried out by Muslims. Prayer is used as the main form of worship that influences the faith and quality of a Muslim's worship. Performing prayer is obligatory for all Muslims. So one form of student contribution in growing the quality of society is by participating in community service activities in Cibeber Village. "Improving the Quality of Prayer Services for Children in Cibeber Village" is one of the titles of the community service program in Cibeber Village. The research method used by the author is qualitative with an ethnographic type of research. This program aims to improve the quality of children's worship, especially in terms of prayer, as well as fostering a spiritual spirit in children by providing understanding regarding the need to purify (thaharah) before prayer, and reading during prayer. This is done so that children can perform prayers well and correctly according to the science of fiqh and the sciences of worship.